Implementasi Algoritma C 5.0 Pada Analisa Data Potensi Pertanian dan Perternakan - Zamasi, Nurnia (TIN: Terapan Informatika Nusantara, 2021)
The problems faced in UPPT in each region in the form of productive land changing functions into residential areas, industries, and business centers can result in a lack of land area for farming and livestock and bad weather conditions. One way to analyze the data is to apply or use data mining techniques. Where data mining is the process of analyzing large data into information to determine the pattern of the conclusions of the data being analyzed. The application of the C. 50 method which will later explore existing data and will form a decision tree, By analyzing the data on agricultural and livestock potential, the UPPT provides counseling in which areas are the types of farming and livestock business so that it does not have an impact on people's income and also reduces losses in trying to farm and raise livestock